Cold and low irradiation shape Polylepis reticulata’s seasonal growth and water use dynamics at the Ecuadorian Andean tree line - Carabajo-Hidalgo, Aldemar; Nadal-Sala, Daniel; Poma, Byron; Asbjornsen, Heidi; Crespo, Patricio; Sabaté, Santiago (Frontiers in Plant Science, 2025)
IntroductionPolylepis reticulata is a tree species that grows in the Ecuadorian Andean páramo at 4500 m a.s.l., an environment characterized by low temperatures, elevated cloudiness, and recurrent fog. These environmental stressors result in scarce periods when both photosynthesis and stem growth can occur. Particularly interesting are P. reticulata transpiration, stem growth, and water use efficiency in growth (WUEBAI) dynamics, which may provide valuable insights into the carbon source-sink growth limitation conundrum. Additionally, little is known about P. reticulata’s sensitivity to the different environmental drivers, and its related life traits. MethodsIn this study we quantify the seasonal transpiration, stem growth and WUEBAI patterns of P. reticulata from continuous field measurements on sap flow and stem growth during an entire year. ResultsWe obtained mean annual values of 1.97 ± 0.05 mm2 day-1 for stem growth, 16.47 ± 0.10 dm3 day-1 for transpiration and 1.20 ± 0.05 cm2 m-3 for WUEBAI. Nevertheless, we found a seasonal pattern for these variables. Cold and cloudy conditions led to a reduction in stem growth, with mean values of 1.67 ± 0.12 mm2 day-1 during this season. Concomitantly, transpiration also declined, with mean values of 12.36 ± 0.08 dm3 day-1, reducing WUEBAI, with mean values of 1.35 ± 0.13 cm2 m-3. On the contrary, during the warmer season, when photosynthesis and cambium cell differentiation occurred simultaneously, all the values were higher, with mean stem growth values of 2.58 ± 0.06 mm2 day-1, mean transpiration values of 18.55 ± 0.12 dm3 day-1 and mean WUEBAI values of 1.39 ± 0.16 cm2 m-3, suggesting a sink-driven limitation of tree growth during the cold season.DiscussionHence, our results suggest that P. reticulata’s growth and transpiration patterns are limited by energy availability, rather than water availability. So, expected temperature increases for the next years may enhance P. reticulata’s growth, should water stress not increase.